Involvement of ERCC1 (rs3212986) and ERCC2 (rs1799793, rs13181) polymorphisms of DNA repair genes in breast cancer occurrence in Burkina Faso - Marc Donald Wilfried Adico; Abdou Azaque Zouré; Herman Karim Sombié; Touwendpoulimdé Isabelle Kiendrebeogo; Soayebo Dabré; Lanyo Jospin Amegnona; Bélélé Siméon Bakyono; Lassina Traoré; Teega‐Wendé Clarisse Ouedraogo; Rogomenoma Alice Ouedraogo; Théodora M. Zohoncon; Albert Théophane Yonli; et al. (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Genetic alterations can result in DNA repair defects, increasing susceptibility to breast cancer. The aim of this study was to evaluate the involvement of two DNA repair genes, ERCC1 (rs3212986, GenBank NC_000073.9) and ERCC2 (rs1799793, rs13181, GenBank: NC_000019.10) in the occurrence of breast cancer in Burkina Faso. Methods This case–control study enrolled 128 participants including 64 patients and 64 healthy controls. Genotyping of polymorphisms were performed by real‐time PCR and PCR‐RFLP. Results The heterozygous AC genotype of the ERCC2rs13181 polymorphism was associated with the occurrence of breast cancer when the mutant allele is inherited under the dominant pattern (CC/AC vs AA; OR = 2.74, 95% IC (1.09–6.87); p = .028), but this association became insignificant after the Bonferroni correction (p = .156). No association was observed between ERCC1rs3212986 and ERCC2rs1799793 polymorphisms and breast cancer risk. Conclusion This study showed that the heterozygous genotype (CA) of the ERCC2rs13181 polymorphism may be associated with a risk of breast cancer.